The Analysis of the relationship between a number of factors and high tech export - AYDIN, Muhammed (KDI School, 2018)
This paper investigates the role of number of factors in enhancing high tech export in the world. This study covers a data a panel of 79 countries from 1995 to 2014. The variables found to be significantly and positively associated with high tech export for these countries in the sample are human capital, trade openness, and institutions. On the other hand, the relations between those independent variables; physical investment, FDI per worker, and business environment and dependent variable; high tech export are not clear. These findings suggest that extra efforts should be given focused on policies on improvement at levels of human capital, quality of institutions, and trade openness in order to accelerate high tech export.
Thesis(Master) --KDI School:Master of Development Policy,2018